2016
DOI: 10.1111/jpm.12321
|View full text |Cite
|
Sign up to set email alerts
|

Parents with mental illness – a qualitative study of identities and experiences with support services

Abstract: Accessible summary What is known on the subject? According to estimates more than half of adult mental health service users are parents, but their experiences are largely lacking from research literature. Parental mental illness can often be viewed from a risk perspective. Parents with mental illness and their families have unmet support needs. What this paper adds to existing knowledge? Parents with mental illness want acknowledgement that they can be able and responsible. Many parents adopt an expert b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
23
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 23 publications
2
23
0
2
Order By: Relevance
“…Our study demonstrates that parents with mental illnesses are searching for support from psychiatric services in order to talk to their children about their illness, findings supported by recent work showing that these parents feel responsible for their parenting role and need for support (Jones, Pietilä, Joronen, Simpson, Gray, & Kaunonen, ; van der Ende et al., ), although this is seldom included in their psychiatric treatment. The finding that under‐age children comply when told by their parents to join an intervention in psychiatric services supporting the family is interesting and not observed earlier.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our study demonstrates that parents with mental illnesses are searching for support from psychiatric services in order to talk to their children about their illness, findings supported by recent work showing that these parents feel responsible for their parenting role and need for support (Jones, Pietilä, Joronen, Simpson, Gray, & Kaunonen, ; van der Ende et al., ), although this is seldom included in their psychiatric treatment. The finding that under‐age children comply when told by their parents to join an intervention in psychiatric services supporting the family is interesting and not observed earlier.…”
Section: Discussionsupporting
confidence: 82%
“…Jones, Pietilä, Joronen, Simpson, Gray, & Kaunonen, 2016;van der Ende et al, 2016), although this is seldom included in their psychiatric treatment. The finding that under-age children comply when told by their parents to join an intervention in psychiatric services supporting the family is interesting and not observed earlier.…”
mentioning
confidence: 99%
“…Indeed, men and women with mental illness are just as likely to be parents as those without mental illness and more than half of service users and mental health nurses come into contact with, in the UK, are parents (Royal College of Psychiatrists 2014). In our study, published in this issue, we found that the parental role is highly meaningful and motivating, but its significance to service users is disregarded (Jones et al 2016).…”
mentioning
confidence: 61%
“…Overall, the stance towards parents with mental illness fluctuates between ambivalence, i.e. overlooking them, or framing parenting through risk and accountability (Jones et al 2016). From a service perspective, this can lead to a situation where only immediate risk triggers extra support and in the absence of this risk, we overlook the needs of many families.…”
mentioning
confidence: 99%
See 1 more Smart Citation